ANALYSIS OF KNOWLEDGE LEVEL LAWS OF THE GAME RUGBY UNION OF RUGBY ATHLETES PON XX PAPUA - Senja, Qonidah Salsabila; Hongwei, YAN; Wei, Luo (ASEAN Journal of Sport for Development and Peace, 2022)
The purpose of this study was to find out how high the level of knowledge regarding the laws of the game rugby union of Indonesian Rugby players as elite players who participate in National Sports Week (PON) is. The type of this research is descriptive research. The method used is a survey with data collection techniques using true and false tests. Techniques data analysis using quantitative descriptive analysis as outlined in the percentage form. The population in this study were rugby athletes who participated in the PON XX Papua (7 provinces). The women's team: Papua, DKI Jakarta, West Java, Aceh, Bali, Yogyakarta, the men's team: Papua, DKI Jakarta, Yogyakarta, West Java, Banten, and Aceh. The sampling technique used random sampling with a total of 55 rugby athletes. The instrument adopted the Laws of the Games Rugby Union exams by World Rugby obtained 35 valid items with a significant level of 5%, the value of rtable = 0.2441, and reliability of 0.718. The research instrument trials were conducted on 15 athletes in Pra-PON Bali. Based on the results of the study obtained the level of knowledge Laws of the Game Rugby Union of Rugby Athletes PON XX Papua the very high category by 12.75%, in the high category by 40.00%, the medium category is 43.64%, the low category is 3,64% and the category deficient at 0.00%. This study is the first study to examine the understanding of the rules of playing Rugby on a national scale (Indonesia) to evaluate elite professional athletes to prepare athletes for a higher level by balancing cognitive factors (understanding of the rules of the game of Rugby) and psychomotor.